Thermal Conductivity of Teak Wood from Thinned Stands - Veriawan Setyo Wibowo; Joko Sulistyo (Masyarakat Peneliti Kayu Indonesia, 2015)
Wood has been utilized as a heat conductor or insulator. Hence, this research aims to discover the thermal conductivity of teak wood using thinned stands from the Perhutani plantation forest. The samples obtained had varying moisture content and fiber direction, and were of distinct tree ages, at 12, 15, 20, 25, and 60 years. This result show that the thermal conductivity in air-dry conditions and fiber saturation points were 0.116 to 0.128 and 0.338 to 0.151 in W/Mk, respectively. The analysis of variance showed that the thermal conductivity of teak wood was affected by the interaction of fiber directions and moisture content but not significantly by tree age. Also, there was a weak relationship found between thermal conductivity and specific gravity in air-dry conditions and longitudinal direction.